THE EFFECT OF LEVERAGE AND INVESTMENT DECISIONS ON FINANCIAL DISTRESS WITH GOOD CORPORATE GOVERNANCE AS MODERATING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE IDX IN 2016-2020 - Safira Permata Adi; Yulia Efni; Fitri Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2022)
This study aims to examine the effect of leverage and investment decisions on financial distress, with good corporate governance as a moderating variable. The population in this research were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016–2020. Purposive sampling was used to determine the sample, which was obtained from 32 companies. The type of data used in this research was secondary data obtained from IDX and the annual report. The analytical method used was logistic regression and moderating analysis with the help of SPSS software to process the data. This study concluded that leverage and investment decisions significantly influence financial distress. On the other hand, good corporate governance does not significantly influence financial distress. GCG cannot moderate the effect of leverage and investment decisions on financial distress.